2007
DOI: 10.1194/jlr.m600428-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipid rafts and accelerated lipopolysaccharide-induced tumor necrosis factor-α secretion in Abca1-deficient macrophages

Abstract: Lipid rafts on the cell surface are believed to be very important as platforms for various cellular functions. The aim of this study was to know whether defective lipid efflux may influence lipid rafts on the cell surface and their related cellular functions. We investigated macrophages with defective lipid efflux from ATP binding cassette transporter A1-deficient (Abca1-KO) mice. Lipid rafts were evaluated by the following two novel probes: a biotinylated and protease (subtilisin Carlsberg)-nicked derivative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
99
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 33 publications
(40 reference statements)
15
99
0
Order By: Relevance
“…To investigate whether the disruption of lipid membrane microdomains leads to inhibition on macrophage response to LPS, BMDMs were cultured in the presence of 10 mM 2OHp␤CD, and their TNF-␣ production into culture supernatants was quantified as previously described (26). We confirmed that this concentration of 2OHp␤CD did not affect cell viability using MTT and lactate dehydrogenase assays (data not shown).…”
Section: Disruption Of Lipid-rich Microdomains Negates the Enhanced Tmentioning
confidence: 51%
“…To investigate whether the disruption of lipid membrane microdomains leads to inhibition on macrophage response to LPS, BMDMs were cultured in the presence of 10 mM 2OHp␤CD, and their TNF-␣ production into culture supernatants was quantified as previously described (26). We confirmed that this concentration of 2OHp␤CD did not affect cell viability using MTT and lactate dehydrogenase assays (data not shown).…”
Section: Disruption Of Lipid-rich Microdomains Negates the Enhanced Tmentioning
confidence: 51%
“…ABCA1 also functions as an antiinflammatory receptor for apoA-I in macrophages via a mechanism that involves the activation of Janus kinase 2 and signal transducer and activator of transcription 3 signaling pathways (24,25). Conversely, macrophages from Abca1 2/2 mice have an increase in both cholesterol content and lipid raft microdomains that activate proinflammatory signaling pathways and up-regulate the expression of cytokines, chemokines, growth factors, scavenger receptors, and TLRs (24,(26)(27)(28). ABCA1 is also expressed by type I and type II alveolar epithelial cells in the lung, where it plays a major role in surfactant metabolism and lipid homeostasis (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers agree that ABCA1 is not located in lipid rafts and that it mediates cholesterol efflux primarily from non-raft domains (52)(53)(54). ABCA1 activity seems to destabilize lipid rafts and has been shown to promote the transfer of FC from the raft to the non-raft domain in BHK cells (55), and Abca1-deficient macrophages are reported to have more lipid rafts (56).…”
Section: Discussionmentioning
confidence: 99%